Experiences and needs of mothers of babies diagnosed with Hypoxic Ischaemic Encephalopathy due to birth asphyxia - Naidoo, Mandy (Stellenbosch : Stellenbosch University, 2016)
Thesis (MPhil (Rehabilitation))--Stellenbosch University, 2016.